Local lattice strain around alloying element and martensitic transformation in titanium alloys - Morinaga M.; Yukawa H.; Yoshino M. (MATEC Web of Conferences, 2020)
Local strain is introduced into the lattice around solute atom due to the size mismatch between solute and solvent atoms in alloy. In this study, local lattice strains are calculated for the first time in titanium alloys, using the plane-wave pseudopotential method. As an extreme case, the local lattice strain around a vacancy is also calculated in various bcc, fcc and hcp metals. It is found that the local strain energy is very high in both bcc Ti and bcc Fe, where the martensitic transformation takes place. From a series of calculations, it is shown that the magnitude of the strain energy stored in the local lattice is comparable to the thermal energy, kBT, where kB is the Boltzmann constant and T is the absolute temperature. Therefore, the presence of local lattice strains in alloy could influence the phase stability that varies largely depending on temperatures. For example, the local lattice strain correlates with the martensitic transformation start temperature, Ms, in binary titanium alloys.